Protein expression on Cr resistant microorganism using electrophoresis method - UMI FATMAWATI; SURANTO SURANTO; SAJIDAN SAJIDAN (Nusantara Bioscience, 2009)
Abstract. Fatmawati U, Suranto, Sajidan. 2009. Protein expression on Cr resistant microorganism using electrophoresis method. Nusantara Bioscience 1: 31-37. Hexavalent chromium (Cr(VI)) is known as toxic heavy metals, so the need is reduced to Cr(III) is much less toxicity. Pseudomonas aeruginosa, Pseudomonas putida, Klebsiella pneumoniae, Pantoea sp., and Saccharomyces cerevisiae are resistant Cr(VI) microorganisms and can reduce Cr(VI). The aim of this research is to know ability of the microorganism to reduce Cr(VI) and to know the protein band pattern between Cr(VI) resistant microorganisms and non-resistant microorganisms inoculated on LB broth. SDS-PAGE was used to identify protein expression. At the same time, Cr(VI) concentration was identified by the 1.5 diphenyl carbazide method. The quantitative data were analyzed by two factorial ANOVA that continued with DMRT at a 1% level test. The qualitative data, i.e., protein expression analyzed by relative mobility (Rf). The results showed that the ability of microorganisms to reduce Cr(VI) at an initial concentration of 0.5 ppm, one ppm, five ppm, and 10 ppm might vary; the average percentage of the ability of each microorganism in reducing Cr(VI) is P. putida (65%) > S. cerevisiae (64.45%) >. P. aeruginosa (60.73%) > Pantoea sp. (50.22%) > K. pneumoniae (47.82%) > without microorganisms (34.25%).ListenRead phonetically The adding microorganisms have significantly influenced toward reduction of Cr(VI). The SDS-PAGE shows that protein expression between resistant and not resistant microorganisms are no different, but resistant microorganisms have more protein (protein band is thicker).